A conversational question and answer chatbot for university - Tham, Zhao Jin (2020)
University admissions have been increasing over each intake. Students and parents who attend University Open Days for information querying are caught in long queues. In addition, University FAQ sites do not always resolve the problems of students and parents. Research has shown that automating information querying using chatbot can resolve operational inefficiencies and FAQ site ineffectiveness. This project proposes to develop “A Conversational Question and Answer Chatbot for University” to reduce manual work done by University marketing and promotion teams in handling information querying. Based on existing chatbot systems review, the AI Chatbot Development Methodology was adopted, and Naïve Bayes approach was chosen as the NLP Engine for the chatbot development implementation. Deployment of the chatbot demonstrated that the chatbot was able to handle most conversations in a limited domain. Further stabilization is required to improve the NLP Engine for the chatbot so that all possible user interactions could be handled.